2005
DOI: 10.1055/s-2005-837609
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Vesicostomy Revisited - the Second 15 Years

Abstract: In young infants CV had a less favourable result in the PUV patients than in cases with high-pressure neuropathic bladder with upper tract dilatation and severe urinary tract infection (UTI), where CV provided decompression and prevented deterioration of the renal function. Cutaneous vesicostomy has stood the test of time in our changing paediatric urological practice and it remains a valuable weapon in the armoury of paediatric urologists in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
5
0
5
Order By: Relevance
“…reviewed their experience with Blocksom vesicostomy over the past 15 years including complications. In that study, the reported complications of Blocksom vesicostomy included stenosis (22%), prolapse (6%) and cellulitis (6%) …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…reviewed their experience with Blocksom vesicostomy over the past 15 years including complications. In that study, the reported complications of Blocksom vesicostomy included stenosis (22%), prolapse (6%) and cellulitis (6%) …”
Section: Discussionmentioning
confidence: 96%
“…In that study, the reported complications of Blocksom vesicostomy included stenosis (22%), prolapse (6%) and cellulitis (6%). 6 Regarding cases of chronic urinary retention in elderly patients, the number of patients who cannot be treated successfully with traditional treatments, including transurethral surgery and catheter placement, will increase as a result of the aging of society. Under such circumstances, the use of Blocksom vesicostomy should not be ruled out as a usable treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…1 In one recent study of children with myelomeningocele undergoing CV, the incidence of urolithiasis was 33% with concurrent pyelonephritis in 11% of patients. 2 These “infection stones” are composed of magnesium ammonium phosphate (struvite) formed by bacterial urease activity.…”
Section: Introductionmentioning
confidence: 97%
“…Hoy en día sigue siendo un tratamiento efectivo, útil y necesario en casos seleccionados, aunque sus indicaciones han disminuido y los tratamientos mínimamente invasivos han ocupado parte de su espacio 2 . Las patologías tratadas son muy diversas, como vejiga neurógena, valvas de uretra posterior (VUP), reflujos vesicoureterales de alto grado o síndrome de Prune-Belly 3 .…”
Section: Introductionunclassified
“…Así, nos enfrentamos con vejigas de poca distensibilidad, bajas capacidades y alta presión de apertura del detrusor. Aunque estos cambios revierten en la mayoría de los pacientes tras el cierre de la derivación, en aquellos en los que la derivación ha permanecido abierta más años, o la enfermedad de base es VUP o vejiga neurógena, encontramos que hasta el 25% de los cierres fracasan 3 .…”
Section: Introductionunclassified